Bending technique for improving genetic gain through restricted selection index - CHANDER, SUBHASH; JAISWAL, U C; KHANNA, A S (The Indian Journal of Animal Sciences, 2014)
The ’bending technique’ was proposed for improving genetic gain through restricted selection index and illustrated with the help of live data. The data on age atiirst calving (AFC), first lactation milk yield (FLMY), first calving interval (FCI) and per cent production etliciency (PE) of 100 Holstein Friesian x Hariana (F1) cows belonging to 21 sires. were collected for this study. Selection indices with restriction on 1 trait FCI and 2 traits AFC and FCI, respectively, were constructed. Estimation of genetic gain in individual trait and overall before and aner modincation of parameter estimates revealed that the overall expected gain with restriction on 1 and 2 traits improved signiticantly after modification of parameter estimates.